The problem of evil in Islam and Christianity: suffering from the philosophical perspectives in Medieval thought - Pawan Ahmad, Isham (Common Ground Publishing, 2009)
The solutions provided to the question of why there is evil range from a denial of absolute evil to a denial of God. The problem of evil weighs heavy on the Abrahamic faiths due to the need to reconcile God's mercy and power with the existence of evil. Although both Christian and Islamic traditions begin their explanation of evil from the Fall of Adam, their interpretation of the repercussions of this event differs. For Christians, Adam was cast out to earth as a punishment for his sin. For the Muslims, on the other hand, Adam had asked God for forgiveness for this transgression and his repentance was accepted and thus, he was forgiven. However, he was still send down to earth not as a punishment but in order to develop his full potential. The Christian response to the problem of evil is dominated on one hand by Augustine's free will argument and its solution God's grace. Irenaeus on the other hand, argues that man is an immature creation that requires earthly experience in order to develop his potential. Combining both Augustine and Irenaeus positions may actually provide a more complete answer and is certainly not contradictory. Muslim philosophers integrated both approaches to get the best of both worlds. They utilized Augustine free will and incorporated Ireneaus' fulfillment of man's potential to argue that life on earth though hard is actually good. These differing understandings of the concept of genesis and the evolution of evil have practical implications on the concept of man responsibility and human action although it is not obvious in everyday life.